IgE+ plasmablasts predict the onset of clinical allergy - Simonin, Elisabeth M.; Babasyan, Susanna; Tarsillo, Justine; Wagner, Bettina (Frontiers in Immunology, 2023)
IgE+ plasmablasts develop following allergen exposure and B cell activation. They secrete IgE and therefore are directly linked to maintain the mechanisms of IgE-mediated allergies. Here, we show that the presence of IgE+ plasmablasts in peripheral blood not only coincides with clinical allergy, but also predicts the upcoming development of clinical disease. Using an equine model of naturally occurring allergy, we compared the timing of allergen exposure, arrival of IgE+ plasmablasts in peripheral blood, and onset of clinical disease. We found that IgE+ plasmablasts predict the development of clinical allergy by at least 3 weeks and can be measured directly by flow cytometry or by IgE secretion following in vitro culture. We also compared the IgE secretion by IgE+ plasmablasts with total plasma IgE concentrations and found that while IgE secretion consistently correlates with clinical allergy, total plasma IgE does not. Together we describe IgE+ plasmablasts as a reliable and sensitive predictive biomarker of allergic disease development.